PENERAPAN BUDAYA POSITIF KESEPAKATAN KELAS DI SMP - Fauziati, Fauziati; Zurita, Isesma; Lizarti, Lizarti; Yetisia, Muetia; Syofyani, Syofyani (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
This research aims to optimize the learning environment in Indonesian language subjects at student through the implementation of a positive culture in the form of